2018
DOI: 10.1534/genetics.118.301692
|View full text |Cite
|
Sign up to set email alerts
|

Probing Cadherin Interactions in Zebrafish with E- and N-Cadherin Missense Mutants

Abstract: Cadherins are cell adhesion molecules that regulate numerous adhesive interactions during embryonic development and adult life. Consistent with these functions, when their expression goes astray cells lose their normal adhesive properties resulting in defective morphogenesis, disease, and even metastatic cancer. In general, classical cadherins exert their effect by homophilic interactions via their five characteristic extracellular (EC) repeats. The EC1 repeat provides the mechanism for cadherins to dimerize w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
(162 reference statements)
0
2
0
Order By: Relevance
“…Here we show the two tissues are in intimate contact, apparently without intervening extracellular matrix, and Cdh1 and Ctnna distributions suggest neural plate and EVL adhere to each other. Our antibody labelling suggest Cdh1 is expressed in membranes of both EVL and plate cells, so EVL/neural plate adhesions could be mediated by homophylic Cdh1 interactions, however since heterophylic interactions between Cdh1 and Cdh2 have been shown in mammalian cells (Straub et al, 2011; Labernadie et al, 2017) and suggested in zebrafish embryos (Warga and Kane, 2018) there may also be heterophylic adhesions between EVL and neural plate. None the less, EVL/neural plate adhesions must be either relatively weak or rapidly dynamic to enable the motile plate to move against the static EVL.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Here we show the two tissues are in intimate contact, apparently without intervening extracellular matrix, and Cdh1 and Ctnna distributions suggest neural plate and EVL adhere to each other. Our antibody labelling suggest Cdh1 is expressed in membranes of both EVL and plate cells, so EVL/neural plate adhesions could be mediated by homophylic Cdh1 interactions, however since heterophylic interactions between Cdh1 and Cdh2 have been shown in mammalian cells (Straub et al, 2011; Labernadie et al, 2017) and suggested in zebrafish embryos (Warga and Kane, 2018) there may also be heterophylic adhesions between EVL and neural plate. None the less, EVL/neural plate adhesions must be either relatively weak or rapidly dynamic to enable the motile plate to move against the static EVL.…”
Section: Discussionmentioning
confidence: 74%
“…The protrusions from both layers lie sandwiched in the plane of the interface and do not protrude into the cells of the opposing layer. The distribution of Cdh1 suggests EVL and neural plate cells are likely to adhere to one another through homophylic adhesions and heterophilic Cdh1-Cdh2 adhesions across the tissue interface may also be possible (Ounkomol et al, 2010; Straub et al, 2011; Labernadie et al, 2017; Warga and Kane, 2018).…”
Section: Resultsmentioning
confidence: 99%